2012
DOI: 10.1262/jrd.2012-005
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Influences Maternal mRNA Degradation and Apoptosis in Porcine Parthenotes Developing <i>In Vitro</i>

Abstract: Abstract. Autophagy, an essential process for cellular maintenance, cell viability, and development, is the bulk degradation of proteins and organelles. This study investigated the expression levels of autophagy-related genes and the effect of 3-methyladenine (3-MA, an autophagy inhibitor) or rapamycin (an autophagy inducer) on maternal gene degradation and apoptosis in porcine parthenotes developing in vitro. LC3, which is essential for the formation of autophagosomes, was widely expressed in porcine partheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 50 publications
6
39
0
2
Order By: Relevance
“…This was used as a template to evaluate DNMTs mRNA expression by qRT-PCR. White bar control; light gray bar oocytes cultured in HT-2 toxin (color figure online) parthenotes (Xu et al 2012) that develop in vitro. However, another study also showed that low concentration of rapamycin induced autophagy during in vitro maturation contributes to enhancing the nuclear and cytoplasmic maturation of porcine oocytes (Song et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This was used as a template to evaluate DNMTs mRNA expression by qRT-PCR. White bar control; light gray bar oocytes cultured in HT-2 toxin (color figure online) parthenotes (Xu et al 2012) that develop in vitro. However, another study also showed that low concentration of rapamycin induced autophagy during in vitro maturation contributes to enhancing the nuclear and cytoplasmic maturation of porcine oocytes (Song et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Las proteínas DICER y AGO2 son de origen materno y actúan en el procesamiento de los microRNAs (51) . Ovocitos prior to the activation of the embryonic genome (120) . The work of Xu et al (120) does not indicate whether this process of autophagy acts after the action of the miRNAs, only shows that by adding autophagy inhibitor 3-metiladedina to early embryonic cultures, the expression of maternal mRNA as c-mos, gdf9 and bmp15 remains still in embryonic stages of 4 cells.…”
Section: Efecto Materno Sobre La Degradación De Rnam Maternosmentioning
confidence: 99%
“…Ovocitos prior to the activation of the embryonic genome (120) . The work of Xu et al (120) does not indicate whether this process of autophagy acts after the action of the miRNAs, only shows that by adding autophagy inhibitor 3-metiladedina to early embryonic cultures, the expression of maternal mRNA as c-mos, gdf9 and bmp15 remains still in embryonic stages of 4 cells. It would be interesting to find out whether autophagocityc vacuoles are comprised with the maternal mRNA debris.…”
Section: Efecto Materno Sobre La Degradación De Rnam Maternosmentioning
confidence: 99%
See 2 more Smart Citations